Electrical conduction mechanism and phase transition studies using dielectric properties and Raman spectroscopy in ferroelectric Pb0.76Ca0.24TiO3 thin films - Pontes, F. M.; Pontes, DSL; Leite, E. R.; Longo, Elson [UNESP]; Chiquito, A. J.; Pizani, P. S.; Varela, José Arana [UNESP] (American Institute of Physics (AIP), 2003)
We have studied the phase transition behavior of Pb0.76Ca0.24TiO3 thin films using Raman scattering and dielectric measurement techniques. We also have studied the leakage current conduction mechanism as a function of temperature for these thin films on platinized silicon substrates. A Pb0.76Ca0.24TiO3 thin film was prepared using a soft chemical process, called the polymeric precursor method. The results showed that the dependence of the dielectric constant upon the frequency does not reveal any relaxor behavior. However, a diffuse character-type phase transition was observed upon transformation from a cubic paraelectric phase to a tetragonal ferroelectric phase. The temperature dependency of Raman scattering spectra was investigated through the ferroelectric phase transition. The soft mode showed a marked dependence on temperature and its disappearance at about 598 K. on the other hand, Raman modes persist above the tetragonal to cubic phase transition temperature, although all optical modes should be Raman inactive above the phase transition temperature. The origin of these modes must be interpreted in terms of a local breakdown of cubic symmetry by some kind of disorder. The lack of a well-defined transition temperature suggested a diffuse-type phase transition. This result corroborate the dielectric constant versus temperature data, which showed a broad ferroelectric phase transition in the thin film. The leakage current density of the PCT24 thin film was studied at elevated temperatures, and the data were well fitted by the Schottky emission model. The Schottky barrier height of the PCT24 thin film was estimated to be 1.49 eV. (C) 2003 American Institute of Physics.